1997
DOI: 10.1093/humrep/12.6.1214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abnormal sperm head morphology on the outcome of intracytoplasmic sperm injection in humans

Abstract: The present study was designed to determine the efficacy of intracytoplasmic sperm injection (ICSI) using spermatozoa with abnormal head morphology in 17 cases with total teratozoospermia. A total of 160 oocytes were retrieved and 144 metaphase II oocytes were injected. The fertilization and cleavage rates were 50.7 and 93.2% respectively. Fertilization failure occurred in two couples. A total of 54 embryos were transferred and pregnancy rates per initiated and per embryo transfer cycle were 17.6 and 20.0% res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 17 publications
4
37
0
6
Order By: Relevance
“…1,13,14,17 Tasdemir et al pointed out that morphology is the most valuable parameter in predicting the sperm-fertilizing capacity in vitro. 18 In another study, Menkveld et al revealed that cases with severe teratozoospermia had yielded a lower implantation and ongoing pregnancy rate when compared with cases of normal sperm morphology. 19 Moreover, Tasdemir and associates showed that in 17 patients with 100% teratozoospermia with abnormal sperm heads, only one ongoing pregnancy was achieved (5.88% per cycle).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1,13,14,17 Tasdemir et al pointed out that morphology is the most valuable parameter in predicting the sperm-fertilizing capacity in vitro. 18 In another study, Menkveld et al revealed that cases with severe teratozoospermia had yielded a lower implantation and ongoing pregnancy rate when compared with cases of normal sperm morphology. 19 Moreover, Tasdemir and associates showed that in 17 patients with 100% teratozoospermia with abnormal sperm heads, only one ongoing pregnancy was achieved (5.88% per cycle).…”
Section: Discussionmentioning
confidence: 98%
“…19 Moreover, Tasdemir and associates showed that in 17 patients with 100% teratozoospermia with abnormal sperm heads, only one ongoing pregnancy was achieved (5.88% per cycle). 18 Although the pregnancy rate is extremely low in ICSI cases with absolute teratozoospermia with sperm head defects, ICSI still remains the only method of choice for treating severe male infertility. It is possible that abnormal sperm head morphology reflects structural abnormalities within the cell, which can directly impair the outcome of the ICSI treatment cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that sperm morphology seems to be the best predictor of outcome in spontaneous pregnancy [2,3], intra-uterine insemination (IUI) [1,7] and conventional IVF [21]. Other papers considered sperm morphology as a prognostic factor of male fertility [12,21,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of the sperm head abnormality can be either due to impaired spermatogenesis or damage in the genetic material of spermatogonia and spermatocytes. Tasdemir et al (1997) reported that abnormality in the sperm head morphology reflects abnormality in spermatogenesis. Wyrobek et al (1983) also noted that when male germ cells are exposed in vivo to a test sample, a positive result demonstrates the sample ability to damage spermatogenesis.…”
mentioning
confidence: 99%